1995
DOI: 10.1017/s0021859600084380
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization following surface-applied pig and cattle slurry in France

Abstract: Field experiments were carried out in Brittany (Western France) in 1993 to measure ammonia losses from surface-applied pig and cattle slurry. Experiments were conducted on grass, stubble (wheat and maize) and arable land using a wind tunnel system. Ammonia losses were followed during periods ranging from 20 to 96 h after slurry application. Rates of slurry applied varied from 40 to 200 m 3 /ha. In two experiments, losses from cattle slurry were respectively 75 and 54% of the ammoniacal nitrogen applied in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
2
14

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 14 publications
(10 reference statements)
10
40
2
14
Order By: Relevance
“…When increasing temperature by 58C for each trial, NH 3 losses increased by less than 1%. Results are contrary to studies by Brunke et al (1988), Sommer and Olesen (1991) and Moal et al (1995) who found losses were significantly enhanced when air temperatures increased. Hoff et al (1981) similarly found that increases in temperature resulted in greater losses from hog manure.…”
Section: Model Sensitivity Evaluationcontrasting
confidence: 99%
See 1 more Smart Citation
“…When increasing temperature by 58C for each trial, NH 3 losses increased by less than 1%. Results are contrary to studies by Brunke et al (1988), Sommer and Olesen (1991) and Moal et al (1995) who found losses were significantly enhanced when air temperatures increased. Hoff et al (1981) similarly found that increases in temperature resulted in greater losses from hog manure.…”
Section: Model Sensitivity Evaluationcontrasting
confidence: 99%
“…Laboratory and field experiments, however, can be time consuming and expensive. Empirical models (Moal et al 1995;Menzi et al 1998;Søggard et al 2002;Misselbrook et al 2005) and various mechanistic models (Rachhpal-Singh and Nye 1986;van der Molen et al 1990;Ge´nermont and Cellier 1997;Ni 1999;Wu et al 2003), such as Volt'Air, have been developed to simulate NH 3 losses from fertilizers. Few models, however, have been validated with independent data sets from regions outside the area where they were developed.…”
mentioning
confidence: 99%
“…1c and 3a). The reducing effect of rainfall on NH 3 volatilization has been well documented (Klarensbeek and Bruins 1991;Moal et al 1995).…”
Section: Ammonia Volatilizationmentioning
confidence: 92%
“…Indeed, according to the author, process of volatilization varies with the NH 4 + concentration in the manure, the enzyme activity, the pH, the temperature, and the slurry properties. Complementary to this author, [39] describes in fact, an equilibrium which exists between the concentrations of 4 …”
Section: Correlations Between Parameters Measured In Situ and Nutrienmentioning
confidence: 99%